A centralized coordinated control strategy for distributed generation when microgrid on grid. (October 2019) - Tang, W
Abstract: This paper presents a centralized and coordinated control strategy for microgrid, whose control strategy includes the coordinated control of renewable energy sources (RESs) and energy storage systems (ESSs). To solve the schedulability of distributed generation in a microgrid, when it operates in grid-connected, a multiple operation mode is adopted, through switching the operation mode, the charge/discharge and state of charge (SOC) of ESSs can be maintained, and the loads will be shared by RESs first when microgrid occurs power deficiency, it reduces loss of ESSs. In this paper, a secondary control strategy for the microgrid model by simulated in MATLAB/Simulink, it through switched three modes, improves schedulability of microgrid and realizes SOC balance smoothly. The results show centralized and coordinated control strategy is accurate and useful.